Exploratory Analysis of Predictors Effecting Suicidal Thinking among Inmates Participating in a Prison Treatment Program - Chintakrindi, Sriram; Gupta, Suditi; Gilmore, Andrew (International Journal of Criminology and Sociology, 2023)
In this study, we use a retrospective case–control study design, to compare our outcomes of interest among inmates who have self-reported suicidal ideations (cases) with inmates who do not report suicidal ideations (controls). The sample group included participants admitted into prison treatment programs who have a co-occurring substance abuse and mental disorders. In our multivariate model analyses, we will introduce control variables to understand the magnitude of effect and directionality that control variables, such as demographic and criminal history variables, have in association with our outcome of interest, suicidal ideations. Our results indicate that individuals with stable housing have significantly lower odds of demonstrating suicidal ideations. Finally, we found that individuals with prior weapons offenses and psychiatric hospitalization have higher odds of demonstrating suicidal ideations. We believe these results have implications for the development of research and theory.